Bimbingan Dan Konseling Komprehensif Berbasis Nilai Profetik Sebuah Kajian Sistematis - Istiqomah, Nurul Af’idah; Prasetya, Akhmad Fajar (CV. SINAR HOWUHOWU, 2025)
The development of digital technology has introduced new challenges to education, particularly in the formation of students’ character. Comprehensive Guidance and Counseling (CGC) is regarded as having a strategic role in addressing these challenges; however, its implementation in practice remains predominantly focused on administrative and responsive aspects. This article aims to analyze and synthesize research findings related to the integration of prophetic values—humanization, liberation, and transcendence—within the implementation of Comprehensive Guidance and Counseling in the digital era. This study employs a qualitative descriptive approach using a Systematic Literature Review (SLR) method guided by the PRISMA framework. Literature searches were conducted through Google Scholar, DOAJ, Garuda, and SINTA, covering publications from 2020 to 2025. Out of 68 identified articles, 21 met the inclusion criteria and were analyzed thematically. The findings indicate that the integration of prophetic values strengthens the developmental and preventive orientation of Comprehensive Guidance and Counseling by positioning students as dignified subjects, promoting liberation from psychosocial constraints, and fostering spiritual awareness as a foundation for self-regulation. Furthermore, the utilization of digital media in guidance and counseling services is considered effective when grounded in value-based and ethical principles. Therefore, the integration of prophetic values within digital-based Comprehensive Guidance and Counseling represents a relevant and strategic approach to strengthening students’ character holistically in the digital era.